Education and indigenous peoples. Lines of work with the Mbuti Pygmy people in the Democratic Republic of Congo - Silvio Testa (FahrenHouse, 2012)
The educational challenge with the indigenous peoples of Africa involves the recognition of them and of elements aimed at ensuring their survival. This challenge is complex because it is not possible to address in isolation the education; we must consider other social, cultural and political factors. Is committed to an Ethno-education that values the social elements of the pygmy people, even from an informal education. The aim is to rescue the right of a people to their survival through an Ethno-education that strengthens the internal cultural elements that are being confronted with those from other cultures.